Comparative biomechanical analysis of tibial posterior slope in medial open wedge high tibial osteotomy vs. distal tuberosity osteotomy with and without anterior-posterior screw: a study using porcine tibia - Nibe Yoshiya; Takahashi Tsuneari; Hai Hironari; Matsumura Tomohiro; Takeshita Katsushi (SICOT-J, 2024)
Purpose While increased posterior tibial slope (PTS) is a concern post-medial open wedge high tibial osteotomy (MOWHTO), the ability of distal tuberosity osteotomy (DTO) to maintain postoperative PTS after cyclic loading remains unverified. This study aims to determine whether PTS alterations significantly differ between DTO and MOWHTO following cyclic loading. Methods: Biomechanical evaluations were conducted on thirty porcine tibias using MOWHTO and DTO, with and without an anterior-posterior (AP) screw. To investigate PTS changes, cyclic testing was carried out for MOWHTO and DTO. Displacement along the mechanical axis during cycles 10th, 100th, 500th, 1000th, 1500th and 2000th, variations in anterior and posterior gaps after 2000 cycles and increased PTS after 2000 cycles, were compared across the three groups. The displacement was evaluated by repeated-measures analysis of variance (ANOVA), and changes in AG and PG and increased PTS were evaluated by one-way ANOVA. The sample size for α and β errors were <0.05 and <0.20, and the effect size was 0.60 for one-way ANOVA and 0.46 for repeated-measures ANOVA. Results: There were no significant differences in displacement and anterior gap changes among the groups. A significant difference was observed in the posterior gap changes (P < 0.001) and increased PTS (P = 0.013) among the groups. Post hoc analysis indicated substantial disparities between MOWHTO and DTO without the AP screw (P = 0.035), as well as between MOWHTO and DTO with the AP screw (P = 0.021) concerning the increased PTS. Conclusion: After cyclic loading, MOWHTO exhibited a notably smaller PTS change than DTO regardless of the presence of an AP screw.